Damage in face-brick facades placed between concrete slabs. (July 2020) - Diaz, C.; Cornadó, C.; Albareda, A.
Abstract: In recent decades, non-structural exposed brick facades have been widely used in Spain and other European and American countries. However, when they are partially supported by floor slabs, to give the image of a continuous element, they present problems that can lead to risks such as collapse and detachment of ceramic pieces. In this article, twenty-two affected buildings located in several Spanish cities were analyzed to determine the parameters that induce risk situations, and to identify the causes of each type of damage. The aim was to verify, using data extracted from real behavior of the facades under analysis, the fragility of most analytical models that have been adopted, in order to avoid anomalies. Consequently, the aim was also to obtain a more reliable starting point for future diagnosis and, when necessary, repair of such vulnerable face brick facades. Highlights: Damage in non-structural face-brick facades can lead to risks such as collapse and detachments. Real cases of damage in face-brick facades placed between concrete slabs are studied. A classification and analysis of actual damage is carried out. Causes of damage are provided.